2010
DOI: 10.1007/s11224-010-9652-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen adsorption on Ti containing organometallic structures grafted on silsesquioxanes

Abstract: The adsorption of hydrogen molecule on a novel structure of Ti containing organometallic complexes grafted on silsequioxanes (SQ, H 8 Si 8 O 12 ) was investigated by means of DFT method. The hydrogen adsorption properties of the complex structures TiRH 7 Si 8 O 12 (R = C 4 H 3 , C 5 H 4 , C 6 H 5 ) keep almost the same as that of corresponding Ti containing organometallic complexes. Moreover, these complex structures can avoid the problem of transition metal clustering which is a disadvantage for hydrogen adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In the geometry optimization, all the structural parameters were fully optimized with an energy convergence of 2.0 × 10 −5 hartree. The accuracy of the computational method was discussed in detail in our previous paper on the hydrogen‐storage property of organometallic complex systems 52.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In the geometry optimization, all the structural parameters were fully optimized with an energy convergence of 2.0 × 10 −5 hartree. The accuracy of the computational method was discussed in detail in our previous paper on the hydrogen‐storage property of organometallic complex systems 52.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In the next theoretical paper, Bao et al [276] investigated by DFT the hydrogen storage property of Ti containing organometallic complexes grafted on silsesquioxanes of the structure TiRH 7 Si 8 O 12 (R = C 4 H 3 , C 5 H 4 , C 6 H 5 ). The results of this study showed that 3d transition metal grafted silsesquioxane complexes can be used as hydrogen storage material.…”
Section: Issuementioning
confidence: 99%
“…Thus, solid-state hydrogen storage is the only available way for mobile applications since it is physically and chemically stable, quickly reversible, cost-efficient, and has high volumetric energy density under standard conditions. Researchers have developed many materials for solid-state hydrogen storage including but not limited to metal–organic frameworks, metal hydride carbon nanotubes, organic liquid hydrides, and new hybrid materials. …”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we study silsesquioxane (SQ) nanomaterial as a possible candidate for solid-state hydrogen storage. Silsesquioxane and its derivatives seem well suited for hydrogen storage and have attracted many experimental and theoretical researchers for gas adsorption and hydrogen storage ,, because (1) they are light, stable, and porous; (2) several SQ compounds have been theoretically predicted for encapsulation using transition-state theory; and (3) they can be functionalized with organic and inorganic groups/particles and therefore have tunable properties. ,,, …”
Section: Introductionmentioning
confidence: 99%